Effects of ageratum conyzoides on semen characteristics and sperm morphology in rats exposed to sodium arsenite (2016)
Arsenite is a major environmental toxicant that is well known to cause reproductive injury. The sperm protective potential of Ageratum conyzoides Linn in arsenic-treated rats was carried out in this study taking advantage of the antioxidant constituents and its androgenic activities. Twenty-four male albino rats aged 16 weeks, weighing 225 to 228g were used. They were grouped into 4(A-Da) with each group containing 6 rats. Group A was orally treated with 100mg/kg ethanol leaf extract of Ageratum conyzoides L., daily for 14 days, group B (single oral dose of sodium arsenite 2.5 mg/kg body weight), C (Ageratum conyzoides extract daily for 14 days and sodium arsenite (SA) given on the 14th day) and group D (Propylene glycol as negative control). It was observed that group B had a lower (p<0.05) percentage motility (26.7±6.67%) when compared across the groups while group A had a significantly higher (p<0.05) mean value (63.3±3.33%). The sperm motility of rats in group D was significantly higher (p<0.05) than groups B and C. This implies that A. conyzoides extract had no adverse effect on the sperm motility of the rats and also ameliorates the adverse effect of arsenite on sperm motility. The mean value obtained for sperm liveability, semen volume and Sperm concentration followed a similar pattern although, the differences were not significant (p>0.05) for semen volume and the Sperm concentration of rats across the groups. The total sperm abnormality obtained across the groups ranges between 10.44 and 14.27% with group B treated with sodium arsenite (SA) having the highest value when compared with groups A and D, although, the differences were not significant (P>0.05). The study concluded that ethanol leaf extract of Ageratum conyzoides has no negative effect on sperm motility, liveability characteristics and morphology and also protected spermatozoa against arsenic reproductive toxicity in Wistar strain albino rats.